2019
DOI: 10.15326/jcopdf.6.2.2018.0152
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Lung Function with Nebulized Revefenacin in the Treatment of Patients with Moderate to Very Severe COPD: Results from Two Replicate Phase III Clinical Trials

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 17 publications
5
51
0
1
Order By: Relevance
“…However, in patients with comorbid diabetes, it may be more appropriate to limit the use of ICS to the minority of patients with COPD who might benefit. There were no safety issues identified with the use of revefenacin in patients with cardiac risk factors [7,9]. In a preclinical study, revefenacin was shown to be a high-affinity competitive antagonist at human recombinant muscarinic acetylcholine receptors with kinetic functional selectivity for M 3 over M 2 muscarinic acetylcholine receptors [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in patients with comorbid diabetes, it may be more appropriate to limit the use of ICS to the minority of patients with COPD who might benefit. There were no safety issues identified with the use of revefenacin in patients with cardiac risk factors [7,9]. In a preclinical study, revefenacin was shown to be a high-affinity competitive antagonist at human recombinant muscarinic acetylcholine receptors with kinetic functional selectivity for M 3 over M 2 muscarinic acetylcholine receptors [27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies 0126 (NCT02459080) and 0127 (NCT02512510) were replicate, 12-week, randomized, doubleblind, placebo-controlled, multiple-dose, parallel-group, phase 3 trials, and the design and conduct were described previously [7]. The studies were approved conducted according to the principles of the International Council on Harmonisation of Technical Requirements for Pharmaceuticals for Human Use guideline for good clinical practice [14], and the code of ethics of the World Medical Association's Declaration of Helsinki [15]; written informed consent was obtained from all patients.…”
Section: Study Design and Conductmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the safety profile for revefenacin observed in previous studies: administration of once-daily revefenacin 88 and 175 µg through a standard jet nebulizer was well tolerated and produced clinically and statistically significant improvements in trough forced expiratory volume in 1 second relative to placebo at 12 weeks in 2 identical phase 3 trials of patients with moderate to very severe COPD. 21 A potential limitation of this study is that it did not include patients with COPD who have a higher exposure to the metabolite THRX-195518 than healthy subjects. 6,7 Metabolite levels observed in the healthy subjects receiving the 700-µg revefenacin dose in this study were, however, in excess of those reported in patients with COPD at the therapeutic dose (175 µg) and thus represent a higher exposure than anticipated in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion and exclusion criteria for the three studies have been described previously. 11,12 For the 12-and 52-week studies, we enrolled patients aged at least 40 years with moderate to very severe COPD, a smoking history of at least 10 packyears, a postipratropium FEV 1 /forced vital capacity ratio <0.7, and a postipratropium FEV 1 <80% of predicted normal and >700 ml at screening. Patients with a substantially increased risk for cardiovascular events, such as myocardial infarction within the past 6 months, unstable or In the 12-week studies, up to 40% of patients were permitted concomitant use of LABA (LABA cap, controlled through stratification during randomization) with or without ICS.…”
Section: Patients and Treatmentsmentioning
confidence: 99%